Assessment of the perception of employees on the effective administration of performance management in the Department of Water Affairs and Forestry (DWAF) head office - Molapo, Pogiso (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2007.